Sacituzumab Govitecan for Metastatic Triple‐Negative Breast Cancer: Clinical Overview and Management of Potential Toxicities. (10th July 2021) - Spring, Laura M.; Nakajima, Erika; Hutchinson, Jennifer; Viscosi, Elene; Blouin, Gayle; Weekes, Colin; Rugo, Hope; Moy, Beverly; Bardia, Aditya
Abstract: Patients with metastatic triple‐negative breast cancer have a poor prognosis. Sacituzumab govitecan (IMMU‐132) is an antibody‐drug conjugate that contains the irinotecan active metabolite, SN‐38, linked to a humanized monoclonal antibody targeting trophoblast cell surface antigen 2, which is overexpressed in many solid tumors. In a basket design phase I/II study, sacituzumab govitecan demonstrated promising single‐agent therapeutic activity in multiple cancer cohorts, leading to accelerated approval by the U.S. Food and Drug Administration of sacituzumab govitecan‐hziy (TRODELVY) for the treatment of patients with metastatic triple‐negative breast cancer who had received at least two prior therapies in the metastatic setting. Recently, results of the phase III trial, ASCENT, were confirmatory. There is limited available information on the adverse event management with sacituzumab govitecan needed to maximize the dose and duration of effective therapy while maintaining patient quality of life. This review summarizes the clinical development and the practical management of patients receiving sacituzumab govitecan. Sacituzumab govitecan has a well‐defined and manageable toxicity profile, and rapid recognition and appropriate early and proactive management will allow clinicians to optimize sacituzumab govitecan treatment for patients. Implications for Practice: Sacituzumab govitecan (TRODELVY) is a novel antibody‐drug conjugate composed of the active metabolite of irinotecan (SN‐38) conjugated to a monoclonal antibody targeting trophoblast cell surface antigen 2, an epithelial cell surface antigen overexpressed in many cancers. Because of the rapid approval of sacituzumab govitecan, there is limited available information on adverse event (AE) management with this agent. As such, this article reviews the clinical development of the drug, the AE profile, and provides recommendations regarding AE management to help optimize therapy with sacituzumab govitecan. Abstract : Sacituzumab govitecan (IMMU‐132) is an antibody‐drug conjugate that contains the irinotecan active metabolite, SN‐38, linked to a humanized monoclonal antibody targeting trophoblast cell surface antigen 2 (Trop‐2), which is overexpressed in many solid tumors. This review summarizes the clinical development and the practical management of patients receiving sacituzumab govitecan.